Kontrowersje wokół deizmu - Drozdowicz, Zbigniew (Humaniora. Czasopismo Internetowe, 2020)
The controversies in the title of this paper are related to an attempt of answering the following questions: who was a deist and what does deism express, as well how is it related to atheism, agnosticism, pantheism and theism? The article by professor Antoni Szwed included in this very volume of “Humaniora” makes a voice in the debate on the issue of deism of Matthew Tindal and several other contemporary deists. I do not intend to argue with the views of that author. It is however necessary to say clearly that in the issue of those deists, as well many others opinions and views may vary in often even radically different. It is to be stressed out that the author of this article had presented his opinion on the issue in the title, but also that he presented in it only a fraction of this very comples problem which was and still is deism. For a better understanding of this problem we may recall several other deists and present the controversies surrounding them.